2010
DOI: 10.1016/j.molcel.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chromatin Architecture by the PWWP Domain-Containing DNA Damage-Responsive Factor EXPAND1/MUM1

Abstract: Summary Dynamic changes of chromatin structure facilitate diverse biological events, including DNA replication, repair, recombination, and gene transcription. Recent evidence revealed that DNA damage elicits alterations to the chromatin to facilitate proper checkpoint activation and DNA repair. Here we report the identification of the PWWP domain-containing protein EXPAND1 as an architectural component of the chromatin, which in response to DNA damage, serves as an accessory factor to promote cell survival. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 37 publications
(50 reference statements)
0
50
1
Order By: Relevance
“…This is consistent with a previous study, which reports that 53BP1 recruits to DSBs through its tandem Tudor domain but not BRCT domain. 35 Our results therefore do not support a role of BZLF1 as a competitor of 53BP1 for binding to chromatin.…”
Section: Bzlf1 Blocks the Formation Of 53bp1 Focicontrasting
confidence: 73%
See 1 more Smart Citation
“…This is consistent with a previous study, which reports that 53BP1 recruits to DSBs through its tandem Tudor domain but not BRCT domain. 35 Our results therefore do not support a role of BZLF1 as a competitor of 53BP1 for binding to chromatin.…”
Section: Bzlf1 Blocks the Formation Of 53bp1 Focicontrasting
confidence: 73%
“…22 To determine whether 53BP1 interacts with BZLF1 through BRCT tandem repeats, we performed immunoprecipitation experiment in cells that were co-transfected with plasmids expressing Flag-BZLF1 and HA-53BP1 or HA-53BP1 without the BRCT domain (HA-53BP1ΔBRCT). 35 The results showed that Flag antibodies could only pull down HA-53BP1 but not HA--53BP1ΔBRCT (Figure 1d), which confirmed that 53BP1 associates with BZLF1 through its BRCT domain. To further discriminate between the two possible mechanisms by which BZLF1 interferes with the recruitment of 53BP1 to IRIF, HONE1 cells were transfected with expression plasmids encoding HA-53BP1ΔBRCT and then assayed for 53BP1 recruitment at DNA damage sites following IR.…”
Section: Bzlf1 Blocks the Formation Of 53bp1 Focimentioning
confidence: 59%
“…Notably, previous work established that 53BP1 BRCT domains also mediate binding to p53 (53)(54)(55) and MUM1/ EXPAND1 (39). It will therefore be interesting in future studies to assess whether 53BP1 binding to p53 or MUM1 is affected by USP28 status or vice versa.…”
Section: Discussionmentioning
confidence: 94%
“…Chromatin Fractionation and Immunoprecipitation Experiments-Preparation of chromatin fractions were described previously with modifications (22). Briefly, cells were harvested at the indicated times after treatment and washed once with PBS.…”
mentioning
confidence: 99%